Numerical analysis of prefabricated steel-concrete composite floor in typical LIPSK building = Analiza numeryczna modelu prefabrykowanego stropu zespolonego typowego budynku LIPSK - Lacki, Piotr; Kasza, Przemysław; Derlatka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the work was to perform numerical analysis of a steel-concrete composite floor located in a LIPSK type building. A numerical model of the analytically designed floor was performed. The floor was in a six-storey, retail and service building. The thickness of a prefabricated slab was 100 mm.
Keywords: steel-concrete composite floor; FEM; numerical analysis; LIPSK type building; strop zespolony; MES; analiza numeryczna; budynek typu LIPSK